A Comparative Investigation of Anaphoric Reference Devices in Anglo-Norman and Middle English Personal Letters - Marcus, Imogen (Studia Anglica Posnaniensia, 2022)
This paper compares the use of anaphoric reference terms, such as le dit (and its English equivalent the said), a characteristic feature of ‘curial style’, in Anglo-Norman (hence AN) and Middle English (hence ME) personal letters. Whilst we know that this style was prevalent in the official AN letters that were used to conduct English parliamentary business until the end of the 1300s, we do not yet have a clear understanding of the extent to which it was prevalent in both AN and ME personal letters, defined here as being written to one addressee who was known to the writer. The results show that there more anaphoric reference terms in the AN epistolary material than in the ME, and that the difference is statistically significant. However, these anaphoric reference devices are very much in evidence in the ME material as well, albeit in smaller numbers, suggesting a degree of influence, or emulation, or both. It is furthermore suggested that the use of anaphoric reference devices in both the AN and ME personal letters is more similar to their use in the literary texts discussed by Burnley (1986) than to their use in their more official, administrative epistolary forebears, i.e., they are often used in a looser, relaxed way, as a kind of ‘connective convenience’ (Burnley 1986: 610). Results relating to diachronic variation demonstrate that the reference terms are most common in the latest (1380s) AN letters and earliest (pre-1431) ME letters, perhaps suggesting a period of overlap. In relation to geographic distribution, ME anaphoric reference terms appear to be used more in letters written in London and Oxfordshire than in the East Anglian or Northern letters. Finally, in the AN corpora, the anaphoric reference devices are most frequently used by writers from the gentry and professions, a finding mirrored in the ME material. Overall, the paper highlights the importance of taking different discoursal contexts, and the deliberate emulation of styles within those contexts, into account when investigating the interaction between Anglo Norman and Middle English during the medieval period.